2022
DOI: 10.1038/s41597-022-01273-x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a large-scale dataset of flood fatalities for territories in the Euro-Mediterranean region, FFEM-DB

Abstract: This data paper describes the multinational Database of Flood Fatalities from the Euro-Mediterranean region FFEM-DB that hosts data of 2,875 flood fatalities from 12 territories (nine of which represent entire countries) in Europe and the broader Mediterranean region from 1980 to 2020. The FFEM-DB database provides data on fatalities’ profiles, location, and contributing circumstances, allowing researchers and flood risk managers to explore demographic, behavioral, and situational factors, as well as environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…The role of gender in shaping vulnerability is controversial and subject to many interpretations (Cutter and Emrich, 2006;de Brito et al, 2017;. While some studies consider women as being particularly vulnerable, especially in the aftermath of floods in low-income countries (Fatouros and Capetola, 2021), a large-scale database of flood fatalities in Europe found that most flood victims are men under 50 years and who are in good health conditions (Papagiannaki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The role of gender in shaping vulnerability is controversial and subject to many interpretations (Cutter and Emrich, 2006;de Brito et al, 2017;. While some studies consider women as being particularly vulnerable, especially in the aftermath of floods in low-income countries (Fatouros and Capetola, 2021), a large-scale database of flood fatalities in Europe found that most flood victims are men under 50 years and who are in good health conditions (Papagiannaki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While CCI insights can guide equitable strategies, there is a risk of unintended consequences. For example, existing impact databases often overrepresent Europe and the United States (e.g., Kreibich et al., 2023; Papagiannaki et al., 2022), leading to an incomplete understanding of CCI patterns in the Global South. Likewise, when using impact data sets derived from newspaper articles (e.g., de Brito et al., 2020; Sodoge, Kuhlicke, & de Brito, 2023; Stahl et al., 2016), minority perspectives can be marginalized as media representations often prioritize the concerns of powerful groups (Orgad, 2012).…”
Section: Pathways For Future Researchmentioning
confidence: 99%
“…As they are data obtained from documentary sources, their time resolution is daily: The day of landslide occurrence is available for all cases, while the hour is quoted only in a few cases. As is widely known in the literature, catalogues that can be obtained from documentary sources only include landslides that cause certain damage, especially human losses [52][53][54]. Generally, phenomena that did not cause damage, for example, landslides that occurred in unpopulated areas, are not reported by documentary sources.…”
Section: Historical Rainfall-induced Landslide Geodatabasementioning
confidence: 99%